2018
DOI: 10.1136/gutjnl-2017-314498
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of premalignant gastric lesions: a multicentre prospective cohort study from low incidence regions

Abstract: In a low gastric cancer incidence area, a surveillance programme can detect gastric cancer at an early curable stage with an overall risk of neoplastic progression of 0.3% per year. Use of serological markers in endoscopic surveillance programmes may improve risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 26 publications
3
67
0
1
Order By: Relevance
“…In western countries, despite the decrease in H. pylori prevalence observed among younger generations, H. pylori is responsible for half the burden of all infection‐related cancers 4 . Although incidence rates of gastric cancer are low in most developed countries, 6 mortality rates are high as cancer cases are usually diagnosed at a late stage 7 . Furthermore, the risk of noncardia gastric cancer has been shown to be significantly elevated among migrant populations 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In western countries, despite the decrease in H. pylori prevalence observed among younger generations, H. pylori is responsible for half the burden of all infection‐related cancers 4 . Although incidence rates of gastric cancer are low in most developed countries, 6 mortality rates are high as cancer cases are usually diagnosed at a late stage 7 . Furthermore, the risk of noncardia gastric cancer has been shown to be significantly elevated among migrant populations 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective cohort study on 68 patients at risk of OSCC secondary to a previous head and neck neoplasia, the per-patient sensitivity, specificity, positive and negative predictive values were 63%, 86%, 77% and 76%, compared to conventional gastroscopy. These values have dropped down to 61%, 86%, 77% and 73%, respectively, compared to endoscopy with Lugol staining (Heresbach et al, 2010).…”
Section: Capsule Endoscopymentioning
confidence: 84%
“…A recent multicentre prospective cohort study from the Netherlands and Norway showed that the serological panel (pepsinogen and G‐17) might add additional value in stratifying patients with premalignant conditions of the stomach to those at higher and lower risk for malignant progression (den Hollander et al ., ). Such stratification could lead to a reduction of unnecessary endoscopic surveillance in a large group of patients with a low‐risk profile.…”
Section: Technologies For Early Diagnosismentioning
confidence: 97%
“…Eine landesweite Kohortenstudie aus den Niederlanden an über 90 000 Patienten zeigte 2008, dass die jährliche Inzidenz für das Magenkarzinom im Falle einer atrophischen Gastritis bei ca. 0,1 % liegt, bei Vorliegen von IM bei 0,25 %, bei niedrig-und mäßiggradiger Dysplasie bei 0,6 % und bei hochgradiger Dysplasie bei 6 [10,11].…”
Section: Hintergrundunclassified